2015
DOI: 10.4038/sljas.v20i2.7479
|View full text |Cite
|
Sign up to set email alerts
|

Community structure of zooplankton and trophic status of some inland reservoirs in the low country intermediate zone of Sri Lanka

Abstract: Diversity and abundance of zooplankton in relation to nitrate-N and total phosphorus levels of 20 minor and medium scale reservoirs in the low country intermediate zone of Sri Lanka were studied in June-October 2013. Total phosphorus content ranged from 0.029 mg L -1 recorded in Wendaruwewa reservoir to 0.529 mg L -1 recorded in Karangamuwa reservoir and Nitrate-N content varied from 1.186 mg L -1 recorded in Adukkane reservoir to 5.625 mg L -1 recorded in Anukkane reservoir indicating that all reservoirs stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Pearson correlation analysis indicated that Rotifera population had negative relation (p< 0.01, 0.05) with water temperature (most Rotifer species prefer cold water) (El-Bassat, 1995 andAboul Ezz et al, 2014), total hardness and total alkalinity (r= -0.323, -0.481 and -0.269), but the positive relations were found with nitrate and nitrite (r= 0.281 and 0.383). Similar correlations were recorded by Abdel Mola and Abd El-Rashid (2012), Khanam et al (2014), Menghong et al (2014) and Sangakkara and Wijeyaratne (2015). While Copepoda correlated negatively (p<0.05) with water temperature and total hardness.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Pearson correlation analysis indicated that Rotifera population had negative relation (p< 0.01, 0.05) with water temperature (most Rotifer species prefer cold water) (El-Bassat, 1995 andAboul Ezz et al, 2014), total hardness and total alkalinity (r= -0.323, -0.481 and -0.269), but the positive relations were found with nitrate and nitrite (r= 0.281 and 0.383). Similar correlations were recorded by Abdel Mola and Abd El-Rashid (2012), Khanam et al (2014), Menghong et al (2014) and Sangakkara and Wijeyaratne (2015). While Copepoda correlated negatively (p<0.05) with water temperature and total hardness.…”
Section: Discussionsupporting
confidence: 86%
“…Many zooplankton species disappear with eutrophication are mainly due to toxins produced by algal blooms especially by cyanabacteria blooms and also clogging of their filter feeding apparatus by algal cells (Sangakkara and Wijeyaratne, 2015). This may be attributed to the presence of less number of species of zooplankton in the hydrodrome, which is eutrophic.…”
Section: Resultsmentioning
confidence: 99%
“…Several crops including cinnamon, coconut, paddy and vegetable are cultivated in the riparian areas of this estuary. It is well known that the amount of fertilizer used in agricultural activities in many parts of Sri Lanka are very much higher than the required level, so that excess fertilizer are leached into water bodies increasing their nitrate-N and TDP levels (Sangakkara and Wijeyaratne 2015). Amarathunga et al (2010) reported that N. marina was not present in the upper reaches of the estuary where salinity is zero and also near to sea mouth where salinity is very high.…”
Section: Discussionmentioning
confidence: 99%
“…However, diversity indices of benthic macro invertebrate communities have been used in several studies in order to monitor the environmental conditions (Gamlath and Wijeyaratne 1997;Dahanayaka and Wijeyaratne 2006;Perera et al 2012;Idroos and Manage 2012;Madhushanka et al 2014). In addition, many studies have concentrated on assessment of physicochemical parameters in the aquatic systems of Sri Lanka in order to identify the source and sink areas of pollutants (Sangakkara and Wijeyaratne 2015;Wijeyaratne 2016). Commonly used biotic indices in RBP II technique are accompanied by multivariate approaches that provide information about the spatial and temporal variations of the environmental characteristics of the aquatic environment (Lewin et al 2013;Goldstein 2011).…”
mentioning
confidence: 99%